Proceedings of the 5th International Conference on Electrical Engineering and Information Technologies for Rail Transportation (EITRT) 2021 Novel Traction Drive Technologies of Rail Transportation - Jia, Limin; Qin, Yong.; Liang, Jianying; Liu, Zhigang; Diao, Lijun; An, Min.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book reflects the latest research trends, methods and experimental results in the field of electrical and information technologies for rail transportation, which covers abundant state-of-the-art research theories and ideas. As a vital field of research that is highly relevant to current developments in a number of technological domains, the subjects it covered include intelligent computing, information processing, communication technology, automatic control, etc. The objective of the proceedings is to provide a major interdisciplinary forum for researchers, engineers, academicians and industrial professionals to present the most innovative research and development in the field of rail transportation electrical and information technologies. Engineers and researchers in academia, industry and government will also explore an insightful view of the solutions that combine ideas from multiple disciplines in this field. The volumes serve as an excellent reference work for researchers and graduate students working on rail transportation and electrical and information technologies.
Overview of Multilevel Inverter Topologies and Modulation Methods -- NP voltage control strategy based on 6th harmonic injection for three-level converter -- Research on IGBT Condition Monitoring Based on On-state Voltage Drop -- Hysteresis Optimization and Power Converter Research of Direct Instantaneous Torque Control for SRM -- Simulation strategy of capacitor voltage fluctuation for railway power conditioner based on MMC-RPC topology -- Research on Hydrogen Power Station Accessing to Traction Power Supply System.
Keywords: Transportation engineering; Traffic engineering; Computational intelligence; Control engineering; Application software; Transportation Technology and Traffic Engineering; Computational Intelligence; Control and Systems Theory; Computer and Information Systems Applications; Railroads -- Technological innovations -- Congresses; Railroads -- Data processing -- Congresses; Railroads -- Electronic equipment -- Congresses